The role of implicit person theories and psychological capital in workplace thriving - Levy, Ronit (My University, 2016)
The aim of the current study was to investigate two possible mechanisms that might facilitate thriving in the workplace, namely implicit person theories and psychological capital. These variables were chosen because of their potential to operate in accordance with Barbara Fredrickson’s broaden and build hypothesis, with implicit person theories working to broaden thought-action repertoires, and psychological capital working to build personal resources. The study employed a quantitative, non-experimental, correlational, and cross sectional design. A sample of 226 working adults living in South Africa volunteered to participate in the study. They completed four online questionnaires: a demographic questionnaire; the Thriving at Work Scale; the Implicit Person Theories Scale; and the Psychological Capital Questionaire-24 (PCQ-24). To test the hypothesis that implicit person theories and psychological capital jointly facilitate the experience of workplace thriving, a series of correlations, regressions, and mediation analyses were conducted. The results indicated that psychological capital does indeed mediate the relationship between implicit person theories and workplace thriving.
A research report submitted in partial fulfilment of the requirements for the degree of MA by Coursework and Research Report in the field of Organisational Psychology in the Faculty of Humanities, University of the Witwatersrand, Johannesburg, on 8 February 2016
Keywords: Work--Psychological aspects; Industrial psychology; Employee motivation; Organizational commitment